Characteristics and Mineral Content of Sediment at Muara Pulau Kayu (MPK) of Southwest Aceh District - Syahrul Purnawan; Zulkarnain Jalil; Chairul Akmal; Yopi Ilhamsyah (Graduate Program of Syiah Kuala University, 2018)
Study on sediment characteristics and mineral content at Muara Pulau Kayu (MPK) of Southwest Aceh District was conducted to find a general description of grain size and mineral content regarding to hydro-oceanographic process. Sampling was collected at MPK, Southwest Aceh District during March 2016. Purposive sampling method was used to determine 4 sampling sites covering estuary and beach area. Grain size and mineral content were analyzed with a set of sieves and X-Ray Fluorescence (XRF with standard reference mineral). Observation on the grain roundness and sphericity showed that sediment grains are generally more rounded at beach area. Mineral content at MPK are dominated by Si, Fe, K, Ca and Ti that are categorized into volcanic mineral which conclude that sediment at MPK originated from Mount Leuser which was an active volcano in the past.